The Influence of AI Training Program and AI Literacy on Ethical AI Use among AI-Trained Undergraduate Students: Evidence from Higher Education in Cambodia - Chhayna Cheng; Borey Ngoeurn (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to investigate the relationships among AI training program, AI literacy, and ethical AI use among AI-trained undergraduate students in Cambodia. Specifically, it examines the effects of AI training program on AI literacy and ethical AI use, as well as the mediating role of AI literacy. Methodology: A quantitative correlational research design was employed using data collected from 300 AI-trained undergraduate students at BELTEI International University through convenience sampling. The data were analyzed using Microsoft Excel, SPSS, and SmartPLS. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to assess the measurement model, structural model, and mediation effect. Main Findings: The findings found that AI training program significantly enhanced AI literacy and ethical AI use, while AI literacy positively influenced ethical AI use. The structural model explained 33.7% of the variance in AI literacy and 45.4% of the variance in ethical AI use. Additionally, AI literacy significantly mediated the relationship between the AI training program and ethical AI use. Novelty/Originality of this study: This study contributes to responsible AI education in Cambodian higher education by integrating AI training program, AI literacy, and ethical AI use into a PLS-SEM model. It highlights AI literacy as a significant mechanism linking AI training experiences with ethical AI use among undergraduate students. The study extends social science education research by emphasizing the role of higher education in enhancing students’ AI-related knowledge and ethical technology practices. The findings also provide implications for educators and institutions designing AI training programs that promote both technological competence and ethical AI use. Future studies are encouraged to extend this model by examining additional factors and diverse educational contexts.